Integrating economic and evolutionary approaches to polygynous marriage. (26th October 2022) - Anderson, Siwan; Bidner, Chris
Abstract: Abstract: We outline the potential for integrating economic and evolutionary approaches to marriage and the family. Our broad argument is that the approaches share a concern for competition . Evolutionary scholars are concerned with the fitness consequences of competition and economists are centrally concerned with the nature of competition: how the allocation of scarce resources is mediated by potentially complex forms of social interaction and conflicts of interest. We illustrate our argument by focusing on conceptual and empirical approaches to a topic of interest to economists and evolutionary scholars: polygynous marriage. In comparing conceptual approaches, we distinguish between those that emphasise the physical environment and those that emphasise the social environment. We discuss some advantages of analysing marriage through the lens of competitive markets, and outline some of the ways that economists analyse the emergence of rules governing the family. In discussing empirical approaches to polygynous marriage, we describe how a concern for informing contemporary policy leads economists to focus on the consequences of polygyny, and in particular we describe some of the ways in which economists attempt to distinguish causal effects from selection effects.